The Association Between Mindfulness and Hypnotizability: Clinical and Theoretical Implications. Issue 1 (9th July 2018) - Grover, Michelle P.; Jensen, Mark P.; Patterson, David R.; Gertz, Kevin J.; Day, Melissa A.
Abstract : Mindfulness-based interventions and hypnosis are efficacious treatments for addressing a large number of psychological and physical conditions, including chronic pain. However, there continues to be debate surrounding the relative uniqueness of the theorized mechanisms of these treatments—reflected by measures of mindfulness facets and hypnotizability—with some concern that there may be so much overlap as to make the mechanism constructs (and, therefore, the respective interventions) redundant. Given these considerations, the primary aim of the current study was to examine the degree of unique versus shared variance between two common measures of mindfulness facets and hypnotizability: the Five Facet Mindfulness Questionnaire and the Stanford Hypnotic Clinical Scale. A cross-sectional survey was conducted with a sample of ( N  = 154) veterans with heterogeneous chronic pain conditions. Bivariate Pearson correlations were used to examine the associations between the target scales. Results showed that the correlations between the Five Facet Mindfulness Questionnaire scales and Stanford Hypnotic Clinical Scale total score were uniformly weak, although significant negative correlations were found between mindfulness facets of observe and nonreact with hypnotizability ( p s < 0.05). Thus, not only are the mindfulness and hypnotizability constructs unique, but when significantly associated, hypnotic suggestibility corresponds with a tendency to be less mindful. These findings have important implications for future research aimed toward matching patients to the treatment most likely to be of benefit, and suggest that matching patients on the basis of these theoretically derived "unique" moderators may hold potential.